Gene Therapy for Restenosis - What Now, What Next? - Appleby, C. E.; Kingston, P. A. (Current Gene Therapy, 2004)
Late luminal loss after coronary angioplasty has resisted pharmacological and physical attempts at prevention for over twenty years. As a consequence of the resistance of restenosis to traditional therapeutic approaches it has become a popular target for DNA-based treatment modalities. In this review we consider what is currently known of the basic pathophysiology of restenosis and briefly outline the previous attempts to influence the long-term outcome after coronary intervention. We then discuss the animal models of vascular injury that have been used for studies of gene therapy and the vectors that have been applied to the setting of vascular gene transfer before considering the many studies in which the effects of specific gene transfer have been studied in the setting of vascular injury. These transgenes are considered in four broad groupings: those that act by the suppression of cellular proliferation in the vessel wall; those that inhibit cell migration; anti-thrombotic transgenes; and transgenes that have multiple effects within the vessel. We finally consider why, although more than eight years have passed since publication of the first studies of gene transfer to inhibit the vascular responses to endoluminal injury, little progress has been made in translating gene therapy for restenosis into the human setting. Principle reasons for the disappointingly slow clinical implementation of gene therapy for restenosis are an incomplete understanding of the vascular biology of restenosis, the difficulty of translating findings in animal models into the human setting and the technical difficulties incumbent upon localised gene delivery into coronary arteries.
Keywords: smooth muscle